Multicomponent Reactions with Cyclic Tertiary Amines Enabled by Facile C−N Bond Cleavage. (7th April 2017) - Zhu, Qiming; Yuan, Qinghe; Chen, Mingwei; Guo, Mengping; Huang, Hanmin
Abstract: A novel and catalyst‐free multicomponent reaction with cyclic tertiary amines, electron‐deficient aryl halides or heteroaromatic halides, and Na2 S enabled by facile C−N bond cleavage of the cyclic tertiary amines was developed. This direct and operationally simple method can be applied with a wide range of functional groups and provides an efficient and rapid approach to potentially drug‐like products containing amine, azaarene, thioether, or phenol ether functionalities in good to excellent yields. The utility of this method was demonstrated by the rapid synthesis of the analgesic ruzadolane.